THE EFFECT OF TAXATION KNOWLEDGE ON THE COMPLIANCE OF PERSONAL TAXPAYERS (Case Study of Employee Taxpayers in Subang Regency) - Putri Rizki Syafitri; Daeng M. Nazier (Journal of Taxation Analysis and Review, 2022)
Tax is a very important factor in the development of a country. Where taxes are the main source for the state in terms of state revenue, especially in the State Budget. The purpose of taxation itself certainly does not always run smoothly. One of the bases for tax revenue on target is Taxpayer Compliance. Taxpayer compliance can be influenced by several factors, one of the internal factors is tax knowledge. Tax knowledge is a taxpayer's basic understanding of the law, laws, and also the correct tax procedures. Taxpayers will make tax payments if they already know and understand their obligations as a taxpayer. The population in this study are employees who qualify as individual taxpayers registered at KPP Pratama Subang. The sampling technique in this study was to use purposive sampling method totalling 48 employee individual taxpayers, the data was collected by distributing questionnaires. The results showed the coefficient of determination R2 of 0.558 which means that the dependent variable can be explained by the independent variable by 55.8% and the remaining 44.2%. The results of this study conclude that tax knowledge affects individual taxpayer compliance.